2018
DOI: 10.1029/2018je005537
|View full text |Cite
|
Sign up to set email alerts
|

Coordinated Nanoscale Compositional and Oxidation State Measurements of Lunar Space‐Weathered Material

Abstract: Space weathering on airless bodies includes a number of processes, such as micrometeorite impacts and solar wind bombardment, which leads to a variety of microscale to nanoscale alteration features, including vapor deposited layers on grain and rock surfaces and creation of nanophase opaque inclusions. The nanophase inclusions cause reddening and darkening of the visible to near-infrared spectra of space weathered material, features associated with increasing space exposure of many airless body regoliths. On t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 67 publications
2
28
0
Order By: Relevance
“…3). The surfaces of the olivine and LPx in A0114‐4 are oxidized to a depth of 30–50 nm with a calculated Fe 3+ /ΣFe ˜0.4 at the surface (although with very large error bars due to noise; see supplementary material and methods in Van Aken and Liebscher 2002; Burgess and Stroud 2018a), and very small (<5 nm) npFe 0 are observed to a maximum depth of ˜60 nm. In several locations, we were able to confirm that the nanoparticles are indeed metallic.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…3). The surfaces of the olivine and LPx in A0114‐4 are oxidized to a depth of 30–50 nm with a calculated Fe 3+ /ΣFe ˜0.4 at the surface (although with very large error bars due to noise; see supplementary material and methods in Van Aken and Liebscher 2002; Burgess and Stroud 2018a), and very small (<5 nm) npFe 0 are observed to a maximum depth of ˜60 nm. In several locations, we were able to confirm that the nanoparticles are indeed metallic.…”
Section: Resultsmentioning
confidence: 99%
“…The monolayer could show the initial stages of plagioclase rim formation. In lunar plagioclase, complex npFe 0 ‐bearing rims composed of layers only a few nanometers thick have been noted (Burgess and Stroud 2018a).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are two known possible mechanisms by which nanoparticles of Fe,Ni metal can form in a parent body environment, specifically space weathering of Fe‐bearing silicates (Thompson et al. 2016; Burgess and Stroud 2018) and by shock melting of Fe‐bearing silicates (e.g., Guo et al. 2020).…”
Section: A Nebular Versus Parent Body Origin Of Feni Carbides In CM mentioning
confidence: 99%
“…This spectral mismatch, which particularly refers to the region between ~0.5 and 2.5 μm, is manifested through a reddened (positive) slope, attenuated absorption features, and darker overall reflectance compared with the fresh unirradiated surface (Chapman, 2004; Clark et al, 2002; Gaffey, 2010). While recent electron microscope analysis has shown that lunar soil contains a variety of Fe (Fe 0 , Fe 2+ , and Fe 3+ ) nanoparticles (Thompson et al, 2016; Burgess & Stroud, 2018), it is the chemically reduced iron nanoparticles (Fe 0 or npFe) created by either solar wind irradiation or micrometeorite impacts that are likely causing this spectral mismatch (e.g., Brunetto et al, 2006; Hapke, 2001; Loeffler et al, 2009; Loeffler et al, 2016; Sasaki et al, 2001). Depending on the size of the npFe, the spectra of the material will appear more sloped (reddened) and, in some cases, darker (Noble et al, 2007).…”
Section: Introductionmentioning
confidence: 99%